Serial brain MRI at 3-6 month intervals as a surrogate marker for Alzheimer's disease - Bradley, K; Bydder, G; Budge, M; Hajnal, J; White, S; Ripley, B; Smith, A (British Institute of Radiology, 2002)
A surrogate marker is needed for Alzheimer's disease (AD) both to aid diagnosis and to assess interventions. Despite widespread use, brain imaging markers have largely been confounded by overlap with "normal" ageing. 39 elderly subjects completed up to four serial volumetric brain MRI scans with intervals from 2.5 months to 7 months. By National Institute of Neurological and Communicative Disorders and Stroke (NINCDS) criteria, five subjects had probable AD, two possible AD and 32 were negative for AD, although this group included memory-impaired subjects. Total brain and ventricular volumes were measured for each scan, and rates of change for each interval calculated. The rate of change in ventricle-to-brain ratio was 15.6% per year (standard deviation (SD) 2.8%) for probable AD compared with 4.3% per year (SD 1.1%) for negative AD (p<0.001). There was no significant difference between these groups' mean ventricle-to-brain ratios measured at a single time point (p=0.25). Rates of change in brain or ventricular volume over time also differed between the two groups (p<0.001). Power calculations reveal that to detect a 20% reduction in the excess rate of atrophy of a probable AD cohort in just 6 months, with 90% power, 135 subjects would be required in each arm of a randomized placebo controlled trial. For a 30% reduction in the excess rate of atrophy, 61 subjects would be required. Rate of change analysis makes serial brain MRI a valuable surrogate marker for Alzheimer's disease. Since only 6 months or less is required between scans, this procedure has both clinical relevance and potential for monitoring interventions.